Analisis Pembiayaan Perbankan Pada Usaha Mikro, Kecil, dan Menegah Terhadap Pertumbuhan Ekonomi Indonesia - Hijrasil Hijrasil; Bahrun Thalib; Abi Suar; Muhdar Muba (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine how much bank financing/credit for micro, small, and medium enterprises can affect Indonesia's economic growth. The results of this study indicate that financing or credit for MSMEs affects economic growth both positively and negatively.